Crystallization and preliminary X-ray diffraction analysis of a biologically active fragment of CD55. - Lea, S; Powell, R; Evans, D (1999)
Crystals have been grown of two of the domains of CD55. This is the first report of crystallization of a short consensus repeat (SCR) domain containing protein. CD55 is a widely expressed polymorphic glycoprotein, which functions as a complement regulator by inhibiting assembly and promoting destruction of C3 and C5 convertases. As a key regulator of complement, CD55 is implicated in the hyperacute rejection of xenografts from pigs into primates. It is also commonly hijacked as a receptor by viruses (e.g. medically important echoviruses and coxsackieviruses) and bacterial pathogens (e.g. certain pathogenic strains of Escherichia coli). Here, crystallization of a virus-binding fragment expressed in yeast, consisting of two of the four extracellular SCR domains of CD55, is reported. The recombinant domains have been crystallized in 30% polyethylene glycol (PEG), 0.2 M sodium acetate, 0.1 M sodium acetate trihydrate pH 4.6 using the sitting-drop vapour-diffusion method. Two crystal forms are observed (orthorhombic and monoclinic) and a native data set to 1.65 A resolution has been collected from the monoclinic form at the Synchrotron Radiation Source, Daresbury, UK.